ADDRESSING GENDER-BASED VIOLENCE BY ANALYZING CRIMES AGAINST WOMEN IN INDIA (2001–2021) FOR A VIKSIT BHARAT 2047 - Patil, Harshali; Tiwari, Arya Brijesh; Singh, Anant Manish; Singh, Kinjal Prithviraj (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Gender-based violence remains a significant barrier to achieving gender equality in India with crimes against women consistently increasing over the years. As India envisions becoming Viksit Bharat by 2047 addressing gender inequality and combating gender-based violence are critical priorities. Crimes against women not only hinder social progress but also undermine the nation’s potential for inclusive growth. In 2023, India ranked 128th position among 177 nations on the Women, Peace and Security (WPS) Index, achieving a score of 0.595 on a scale of 1. This research highlights the alarming trends and patterns of crimes against women in India between 2001 and 2021 offering evidence-based insights for researchers and activists. While existing literature highlights the challenges of gender-based violence, there is limited research that integrates 20 years of crime data with actionable insights for activists and stakeholders. This study fills that gap by offering a state-wise and category-specific analysis of crimes using a visual dashboard contributing to the goal of building a developed and equitable India by 2047. The objective of this research is to analyse two decades of crime data to uncover trends, identify high-incidence states and crime types and evaluate systemic factors like legal effectiveness and public awareness. A dataset on crimes against women in India was sourced from Kaggle covering the years 2001 to 2021. Data preprocessing and analysis were conducted using Microsoft Excel focusing on key metrics such as total crime volume, crime rates per 100,000 women, conviction rates and response times. This research underscores the need for robust, region-specific policies to address gender-based violence emphasizing law enforcement efficiency and public awareness.